2017
DOI: 10.4085/1062-6050-49.3.89
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral Osteoarthritis After Surgical or Nonsurgical Treatment of Anterior Cruciate Ligament Rupture: A Systematic Review

Abstract: Although OA prevalence was higher in the surgical treatment group at a mean follow-up of 11.8 years, no definitive evidence supports surgical or nonsurgical treatment after anterior cruciate ligament injury to prevent posttraumatic OA. Current studies have been limited by small sample sizes, low methodologic quality, and a lack of data regarding confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 92 publications
(150 reference statements)
0
52
0
10
Order By: Relevance
“…Individuals with ACL injury are at high risk of poor longterm outcomes (eg, osteoarthritis, [18][19][20] knee pain, 21 diminished quality of life [21][22][23] ), and early symptoms predict more severe knee pain and symptoms 6 years after an ACL injury. 24 Furthermore, preoperative knee and body pain are important predictors of postsurgical outcomes 1 or 2 years after an ACL reconstruction.…”
mentioning
confidence: 99%
“…Individuals with ACL injury are at high risk of poor longterm outcomes (eg, osteoarthritis, [18][19][20] knee pain, 21 diminished quality of life [21][22][23] ), and early symptoms predict more severe knee pain and symptoms 6 years after an ACL injury. 24 Furthermore, preoperative knee and body pain are important predictors of postsurgical outcomes 1 or 2 years after an ACL reconstruction.…”
mentioning
confidence: 99%
“…Anterior cruciate ligament injury and reconstruction surgery (ACLR) dramatically increase the risk of developing knee osteoarthritis (OA), with 30-50% of patients developing OA within two decades (7,20). Though the causes of knee OA are poorly understood, a growing body of evidence implicates chronic quadriceps dysfunction as a critical contributor (2,9,29,34).…”
Section: Introductionmentioning
confidence: 99%
“…There may also be long-term consequences of ACL injury. Radiographic osteoarthritis (OA) may affect up to 71% of patients 10-15 years after their ACLR [158], and the prevalence of OA is similar, irrespective of whether patients have ACLR or not [81].…”
Section: Consequences Of Acl Injurymentioning
confidence: 99%
“…However, having surgical treatment does not automatically lead to satisfactory outcomes, and this may be related to expectations about RTS, knee stability, and ability to recover [213]. In the short term after ACLR, approximately 90% of patients achieved normal or nearly normal knee function regarding strength and stability [13], but in long-term studies a high incidence of OA has been reported [81,158].…”
Section: Outcome After Primary Aclrmentioning
confidence: 99%